2018
DOI: 10.1002/cssc.201800057
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Cost K4Fe(CN)6 as a High‐Voltage Cathode for Potassium‐Ion Batteries

Abstract: Potassium-ion batteries (KIBs) are of interest for large-scale electrical energy storage, owing to the abundance of K resources and potential high energy density. Low-cost cathodes with high performance are crucial for KIBs. Herein, K Fe(CN) is shown to be a low-cost and high-voltage cathode for KIBs. It can deliver a high voltage of approximately 3.6 V and a discharge capacity of 65.5 mAh g with a lifespan of 400 cycles of discharge and charge. This is attributed to the strong σ bonds between C atoms and Fe a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 36 publications
2
23
0
Order By: Relevance
“…Meanwhile, potassium-ion storage systems, including potassium-ion batteries (PIBs) and potassium-ion capacitors (PICs), are also attracting widespread attention for the high natural abundance of potassium resources [35][36][37][38][39] . PIBs can provide a high energy density comparable with LIBs because that the standard electrode potential of K ( −2.93 V vs. SHE) is close to that of Li ( −3.04 V vs. SHE), which are considered to be one of the most promising alternatives [40][41][42] .…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, potassium-ion storage systems, including potassium-ion batteries (PIBs) and potassium-ion capacitors (PICs), are also attracting widespread attention for the high natural abundance of potassium resources [35][36][37][38][39] . PIBs can provide a high energy density comparable with LIBs because that the standard electrode potential of K ( −2.93 V vs. SHE) is close to that of Li ( −3.04 V vs. SHE), which are considered to be one of the most promising alternatives [40][41][42] .…”
Section: Introductionmentioning
confidence: 99%
“…As the size of K + (1.38 Å) is much larger than Na + (1.02 Å) and Li + (0.76 Å) 25 , large migration channels and stable crystal structures are essential for K ion migration, which raises a great challenge to develop suitable cathodes. Among the cathode materials reported for KIBs , Prussian blue analogs (PBAs) have received most intensive studies with good capacity and favorable cycling stability because of their 3D open framework structures 14,[31][32][33][34][35][48][49][50] . For instance, Goodenough et al reported a cyanoperovskite K x MnFe(CN) 6 (0 ≤ x ≤ 2) cathode for KIBs, delivering a stable discharge capacity of~100 mAh g −1 and a capacity retention of 91% over 100 cycles 33 .…”
mentioning
confidence: 99%
“…In addition, the upper cutoff voltage allowed for most K-layered oxides is limited due to the structural instability and the concomitant capacity loss at deep charge [5,[23][24][25]27]. For example, when depotassiating K x MnO 2 and K y CrO 2 to x < 0.2 and y < 0.4, respectively, the crystallinity of electrodes is significantly reduced [5,27] The specific capacity of K-PBAs is slightly lower than that of Na-PBAs because of the heavier K + ions; nevertheless, their higher voltages result in competitive specific energies ( Figure 3b) [8][9][10][33][34][35][36][37][38][39]. There are two known factors that contribute to the voltage difference: (1) the lower anode potential for K + /K than for Na + /Na, and (2) according to density functional theory [40], the interaction between alkali ions and the metal-organic framework strengthens with alkali size, which stabilizes the discharged products and results in an increasing intercalation potential from Li + to Na + (Figure 3e) [10].…”
Section: Layered Oxide Compoundsmentioning
confidence: 99%